Understanding the Impact of Thiophene/Furan Substitution on Intrinsic Charge-Carrier Mobility - YAVUZ, İLHAN (AMER CHEMICAL SOC, 2017)
One of the major challenges in rationalizing the intrinsic influences of molecular fine tuning on charge transport in organic semiconductors is due to changes in molecular packing. Thus, it is, to a limited extent, desirable to elaborate materials to exhibit similar packing arrangements that slightly differ in their molecular structures. A molecular system, consisting of a heterocyclic core flanked by phthalimide end-capping units, is promising to overcome this issue. Previous XRD measurements have revealed that, when the bithiophene (bi-T) core was replaced by bifuran (biF), the molecular packing was largely maintained, while the resulting difference in charge transport was substantial, substituting bi-T with bi-F results in more than 1 order of magnitude increase in hole mobility (i.e., 1.7 X 10(-3) vs 2.6 x 10(-2) cm(2)/(V s)) with a loss in electron mobility (i.e., 0.21 vs 0.0 cm(2)/(V s)). The calculated hole mobilities with the MPW1K/TZ2P methodology are found to be lower for bi-T, as the reorganization energies of bi-T are noticeably higher than those of bi-F due to the nonplanarity of bi-T. MD simulations have shown that the disordered hole mobility predictions are in good agreement with the experimental measurements, for which T -> F substitution results in an increase in hole mobility. In contrast, the difference in electron mobilities with T -> F substitution is predicted to be insignificant, most likely due to the lower average electronic coupling of bi-F. The discrepancy between calculated and experimental electron mobility may originate from macroscopic effects, such as the organic field effect transistor (OFET) device configuration which was not taken into consideration in this study.
Keywords: DENSITY-FUNCTIONAL THEORY; SOLAR-CELLS; ORGANIC SEMICONDUCTORS; OPTOELECTRONIC PROPERTIES; HETEROCYCLIC OLIGOMERS; HOPPING TRANSPORT; ALPHA-OLIGOFURANS; ELECTRON-MOBILITY; SINGLE-CRYSTALS; OLIGOTHIOPHENES